The influence of oxidation debris containing in graphene oxide on the adsorption and electrochemical properties of 1, 10-phenanthroline-5, 6-dione. Issue 9 (4th February 2016) - Ma, Danyang; Dong, Lini; Zhou, Ming; Zhu, Liande
Abstract : The presence of oxidation debris greatly impact on the adsorption and electrochemical response of 1, 10-phenanthroline-5, 6-dione on graphene oxide. Abstract : It is gradually accepted that graphene oxide, which is derived from the exfoliation of graphite oxide that is synthesized by the chemical oxidation of graphite, actually consists of partially oxidized graphene sheets and highly oxidized carbonaceous debris. The quantity of oxidation debris comprises around one third of the total mass of the graphene oxide. The presence of oxidation debris has a significant impact on the physical and chemical properties of graphene oxide. In this article, we address the influence of the oxidation debris on the surface properties of graphene oxide. We discovered that the surface adsorption of organic molecules on graphene oxide was improved greatly after the elimination of the oxidation debris. A typical redox mediator, 1, 10-phenanthroline-5, 6-dione, was studied as the model adsorbed molecule in terms of its adsorption quantity and electrochemical response. After removing the oxidation debris, a five-fold increase in adsorption capacity is achieved on the same amount of graphene oxide. Correspondingly, the electrochemical response for the oxidation of NADH mediated by the adsorbed 1, 10-phenanthroline-5, 6-dione was enhanced as well, which led to improved analytical performances in terms of the sensitivity, linear range and detection limit for the purified graphene oxide modified electrode.